Exome sequencing of Bardet–Biedl syndrome patient identifies a null mutation in the BBSome subunit BBIP1 (BBS18). Issue 2 (11th September 2013) - Scheidecker, Sophie; Etard, Christelle; Pierce, Nathan W; Geoffroy, Véronique; Schaefer, Elise; Muller, Jean; Chennen, Kirsley; Flori, Elisabeth; Pelletier, Valérie; Poch, Olivier; Marion, Vincent; Stoetzel, Corinne; et al.
Abstract : Background: Bardet–Biedl syndrome (BBS) is a recessive and genetically heterogeneous ciliopathy characterised by retinitis pigmentosa, obesity, kidney dysfunction, postaxial polydactyly, behavioural dysfunction and hypogonadism. 7 of the 17 BBS gene products identified to date assemble together with the protein BBIP1/BBIP10 into the BBSome, a protein complex that ferries signalling receptors to and from cilia. Methods and results: Exome sequencing performed on a sporadic BBS case revealed for the first time a homozygous stop mutation (NM_001195306: c.173T>G, p.Leu58*) in the BBIP1 gene. This mutation is pathogenic since no BBIP1 protein could be detected in fibroblasts from the patient, and BBIP1[Leu58*] is unable to associate with the BBSome subunit BBS4. Conclusions: These findings identify BBIP1 as the 18th BBS gene ( BBS18 ) and suggest that BBSome assembly may represent a unifying pathomechanism for BBS.